2017
DOI: 10.1186/s12889-017-4490-6
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of a school-based comprehensive malaria program in primary schools in Sikasso region, Mali

Abstract: BackgroundThe expansion of malaria prevention and control to school-aged children is receiving increasing attention, but there are still limited data on the costs of intervention. This paper analyses the costs of a comprehensive school-based intervention strategy, delivered by teachers, that included participatory malaria educational activities, distribution of long lasting insecticide-treated nets (LLIN), and Intermittent Parasite Clearance in schools (IPCs) in southern Mali.MethodsCosts were collected alongs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
(40 reference statements)
1
10
0
Order By: Relevance
“…Even when interpreted with appropriate caution, the observational analyses presented here indicate that the annual IRS campaigns from 2012 to 2015 in the Ségou Region of Mali were good public health investments. Around half a million people were protected for 3 years at a rough cost of around 7.00 USD or less per person per year regardless of which product was sprayed—similar to recent estimates of the cost of distributing LLINs to school children (around 5.50 USD per child [ 60 ]) or delivering community-based SMC (around 4.20 USD per child [ 54 ]) in Mali. These same IRS campaigns were also broadly associated in time and space with rapid decreases in malaria incidence and overall An.…”
Section: Discussionsupporting
confidence: 67%
“…Even when interpreted with appropriate caution, the observational analyses presented here indicate that the annual IRS campaigns from 2012 to 2015 in the Ségou Region of Mali were good public health investments. Around half a million people were protected for 3 years at a rough cost of around 7.00 USD or less per person per year regardless of which product was sprayed—similar to recent estimates of the cost of distributing LLINs to school children (around 5.50 USD per child [ 60 ]) or delivering community-based SMC (around 4.20 USD per child [ 54 ]) in Mali. These same IRS campaigns were also broadly associated in time and space with rapid decreases in malaria incidence and overall An.…”
Section: Discussionsupporting
confidence: 67%
“…Perhaps, this study was the first of its kind to produce findings of exposure based on the needed indicators. However, few school-based studies have focused on changes in students' malaria knowledge and parasitemia [61,62]. In this study, a significant rise (ES = 14.5%) in overall knowledge about malaria and reduction in misconceptions were observed between the two ends.…”
Section: Discussionmentioning
confidence: 62%
“…Schools and school-based education are currently getting global attention for involvement in public health. For example, school-aged children focused on educational and parasitic clearance intervention studies in Mali suggested a comprehensive school-based control strategy as a feasible and affordable way to address the burden of malaria among school children [61,62]. However, there are limited studies focused on demonstrating that teaching students in school increase awareness at home that the current study aimed for.…”
Section: Limitations Of the Studymentioning
confidence: 96%
“…The malaria prevention education component of the intervention was estimated to cost $2.13 per child, and the intermittent parasite clearance to cost an additional $2.72 per child treated. 30 In this trial, a combination of SP/AS was used; however, the use of sulphadoxine-pyrimethamine in combination with amodiaquine as recommended by WHO for seasonal malaria chemoprevention in children under 5 years living in areas of highly seasonal transmission in the Sahel subregion 31 would be preferable and would considerably reduce the cost of treatment. A drug combination with a longer half-life, such as dihydroartemisisin-piperaquine, can provide a longer period of protection against new infections 19 but may be more costly and does not necessarily offer the same advantage in all epidemiological situations.…”
Section: Bmj Global Healthmentioning
confidence: 99%